Annexin A6 regulates interleukin‐2‐mediated T‐cell proliferation. Issue 6 (8th March 2016) - Cornely, Rhea; Pollock, Abigail H; Rentero, Carles; Norris, Sarah E; Alvarez‐Guaita, Anna; Grewal, Thomas; Mitchell, Todd; Enrich, Carlos; Moss, Stephen E; Parton, Robert G; Rossy, Jérémie; Gaus, Katharina
Abstract : Annexin A6 (AnxA6) has been implicated in cell signalling by contributing to the organisation of the plasma membrane. Here we examined whether AnxA6 regulates signalling and proliferation in T cells. We used a contact hypersensitivity model to immune challenge wild‐type (WT) and AnxA6 −/− mice and found that the in vivo proliferation of CD4 + T cells, but not CD8 + T cells, was impaired in AnxA6 −/− relative to WT mice. However, T‐cell migration and signalling through the T‐cell receptor ex vivo was similar between T cells isolated from AnxA6 −/− and WT mice. In contrast, interleukin‐2 (IL‐2) signalling was reduced in AnxA6 −/− compared with WT T cells. Further, AnxA6‐deficient T cells had reduced membrane order and cholesterol levels. Taken together, our data suggest that AnxA6 regulates IL‐2 homeostasis and sensitivity in T cells by sustaining a lipid raft‐like membrane environment.